2018
DOI: 10.3390/ma11122473
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Surface Plasmon Resonance of Lanthanum Hexaboride to Absorb Solar Heat: A Review

Abstract: While traditional noble metal (Ag, Au, and Cu) nanoparticles are well known for their plasmonic properties, they typically only absorb in the ultraviolet and visible regions. The study of metal hexaborides, lanthanum hexaboride (LaB6) in particular, expands the available absorbance range of these metals well into the near-infrared. As a result, LaB6 has become a material of interest for its energy and heat absorption properties, most notably to those trying to absorb solar heat. Given the growing popularity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 97 publications
0
18
0
Order By: Relevance
“…LaB 6 nanoparticles were reported in the literature to have localized surface plasmon resonance (LSPR) absorption bands in the NIR region with the absorption maximum wavelength being particle size dependent. [ 32,33 ] The singlet O 2 was formed most probably via energy transfer from plasmonically excited triplet LaB 6 NCs to ground state molecular oxygen, similar to other nanomaterials. [ 31 ] Efficient energy transfer requires good similarity (or good electronic orbital wave function overlap) between triplet excited LSPR state of a nanomaterial and singlet excited state of molecular oxygen.…”
Section: Resultsmentioning
confidence: 98%
“…LaB 6 nanoparticles were reported in the literature to have localized surface plasmon resonance (LSPR) absorption bands in the NIR region with the absorption maximum wavelength being particle size dependent. [ 32,33 ] The singlet O 2 was formed most probably via energy transfer from plasmonically excited triplet LaB 6 NCs to ground state molecular oxygen, similar to other nanomaterials. [ 31 ] Efficient energy transfer requires good similarity (or good electronic orbital wave function overlap) between triplet excited LSPR state of a nanomaterial and singlet excited state of molecular oxygen.…”
Section: Resultsmentioning
confidence: 98%
“…This special issue is composed of five review articles, five research articles, and two communications. The first part of the latter is devoted to the applications of plasmonics to physics and engineering [29,30,31,32,33]. Concerning the applications to physics, such as non-linear optics, Mattox et al demonstrated the control of plasmonic properties of LaB6 via Eu-doping on a spectral range from near-infrared to infrared [29].…”
Section: Synopsismentioning
confidence: 99%
“…Concerning the applications to physics, such as non-linear optics, Mattox et al demonstrated the control of plasmonic properties of LaB6 via Eu-doping on a spectral range from near-infrared to infrared [29]. Then, Mattox et al presented a review on the tuning of the plasmonic resonance of lanthanum hexaboride for a potential application to solar heat absorption [30]. Besides, Ogata et al investigated the effect of the plasmonic resonance of metallic nanostructures on the optical third harmonic generation (THG) enhancement of nickel nanostructure-covered microcubes [31].…”
Section: Synopsismentioning
confidence: 99%
“…This special issue is composed of five review articles, five research articles, and two communications. The first part of the latter is devoted to the applications of plasmonics to physics and engineering [29][30][31][32][33]. Concerning the applications to physics, such as non-linear optics, Mattox et al demonstrated the control of plasmonic properties of LaB 6 via Eu-doping on a spectral range from near-infrared to infrared [29].…”
Section: Synopsismentioning
confidence: 99%
“…Concerning the applications to physics, such as non-linear optics, Mattox et al demonstrated the control of plasmonic properties of LaB 6 via Eu-doping on a spectral range from near-infrared to infrared [29]. Then, Mattox et al presented a review on the tuning of the plasmonic resonance of lanthanum hexaboride for a potential application to solar heat absorption [30]. Besides, Ogata et al investigated the effect of the plasmonic resonance of metallic nanostructures on the optical third harmonic generation (THG) enhancement of nickel nanostructure-covered microcubes [31].…”
Section: Synopsismentioning
confidence: 99%